1989
DOI: 10.1159/000125109
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor-Like Immunoreactivity, Arginine Vasopressin-Like Immunoreactivity and ACTH-Releasing Bioactivity in Hypothalamic Tissue from Fetal and Neonatal Sheep

Abstract: Corticotropin-releasing factor-like immunoreactivity (CRF-LI), arginine vasopressin-like immunoreactivity (AVP-LI) and ACTH-releasing bioactivity of hypothalamic tissue from 63- to 143-day-old ovine fetuses and from 7- and 150-day-old lambs have been assessed. CRF-LI and AVP-LI contents and concentrations increased steadily between 63 and 138 days of gestation, decreased at day 143 then rose again in postpartum animals. In terms of concentration, the AVP-LI/CRF-LI ratio remained close to 5 between 63 and 123 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Similarly, ex¬ periments using anesthetized rats (3) and conscious sheep (4,5) have demonstrated that concentrations of CRH and AVP in pituitary portal blood increase in response to stress stimuli. The source of these neuropeptide hormones in the rat is the hypophysiotropic CRH neurons originating in the parvocellular part of the hypothalamic paraventricular nucleus (6) and similar neurosecretory pathways are probably also involved in the sheep (7)(8)(9).In addition to these endogenous systems control¬ ling ACTH release, it is well established that exo¬ genous CRH and AVP will stimulate the pituitary/ adrenocortical axis directly in man and synergistic effects of these hormones on ACTH release have also been demonstrated in sheep (10-13). Also, however, studies have been carried out in man where CRH has been given to individuals in whom the release of AVP has been experimentally stimu¬ lated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ex¬ periments using anesthetized rats (3) and conscious sheep (4,5) have demonstrated that concentrations of CRH and AVP in pituitary portal blood increase in response to stress stimuli. The source of these neuropeptide hormones in the rat is the hypophysiotropic CRH neurons originating in the parvocellular part of the hypothalamic paraventricular nucleus (6) and similar neurosecretory pathways are probably also involved in the sheep (7)(8)(9).In addition to these endogenous systems control¬ ling ACTH release, it is well established that exo¬ genous CRH and AVP will stimulate the pituitary/ adrenocortical axis directly in man and synergistic effects of these hormones on ACTH release have also been demonstrated in sheep (10-13). Also, however, studies have been carried out in man where CRH has been given to individuals in whom the release of AVP has been experimentally stimu¬ lated.…”
mentioning
confidence: 99%
“…Similarly, ex¬ periments using anesthetized rats (3) and conscious sheep (4,5) have demonstrated that concentrations of CRH and AVP in pituitary portal blood increase in response to stress stimuli. The source of these neuropeptide hormones in the rat is the hypophysiotropic CRH neurons originating in the parvocellular part of the hypothalamic paraventricular nucleus (6) and similar neurosecretory pathways are probably also involved in the sheep (7)(8)(9).…”
mentioning
confidence: 99%
“…There is a clear developmental influence on its secretion in response to hypotension during fetal life in the sheep (1). Also, AVP is present very early in fetal life (10,11) and appears important in the stimulation of ACTH secretion. Its relationship to the appearance of corticotrophin-releasing factor and its function in the stimulation of ACTH secretion change with development in both the sheep (10) and the rat (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the pituitary portal levels of AVP were elevated in the fetus, resulting in the secretion of ACTH. Brieu et al (10) concluded that AVP is more important in the stimulation of ACTH secretion in fetuses younger than 138 d gestation than at term, with corticotropin-releasing factor assuming a progressively more important role. The fetal cortisol response and its absence in the neonates reflects this ontogenetic phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This normal pattern can be delayed by foetal adrenalectomy, and accelerated by infusion of cortisol into the foetus (Antolovich et al 1988). When cortisol was added to foetal pituitary cells in vitro there was an increase in the ratio of bioactive to immunoreactive ACTH secreted into the culture medium (Brieu et al 1989). The suggestion has been made, therefore, that cortisol exerts a positive feed-forward effect at the level of the foetal pituitary during late gestation to promote changes in foetal pituitary corticotroph histology and to enhance secretion of a form of ACTH (presumably ACTH1-39), with greater biological activity.…”
Section: Activation Of Foetal Pituitary Functionmentioning
confidence: 99%